2020
DOI: 10.1038/s41598-020-78019-5
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-inducible Lrp6-APEX2 interacting proteins identify ESCRT machinery and Trk-fused gene as components of the Wnt signaling pathway

Abstract: The canonical Wnt pathway serves as a hub connecting diverse cellular processes, including β-catenin signaling, differentiation, growth, protein stability, macropinocytosis, and nutrient acquisition in lysosomes. We have proposed that sequestration of β-catenin destruction complex components in multivesicular bodies (MVBs) is required for sustained canonical Wnt signaling. In this study, we investigated the events that follow activation of the canonical Wnt receptor Lrp6 using an APEX2-mediated proximity label… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Wnt signaling causes the uptake of large amounts of extracellular fluid by macropinosomes ( Redelman-Sidi et al., 2018 ; Tejeda-Muñoz et al., 2019 ). In addition, a gene ontology analysis of biotinylated Wnt-induced Lrp6-APEX2 target proteins indicated that LRP6-interacting proteins were involved in actin cytoskeleton remodeling ( Colozza et al., 2020 ). To examine whether Wnt induced changes in the cytoskeleton, primary human corneal stromal (HCSF) fibroblasts ( Gallego-Muñoz et al., 2018 ) were treated with Wnt3a.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt signaling causes the uptake of large amounts of extracellular fluid by macropinosomes ( Redelman-Sidi et al., 2018 ; Tejeda-Muñoz et al., 2019 ). In addition, a gene ontology analysis of biotinylated Wnt-induced Lrp6-APEX2 target proteins indicated that LRP6-interacting proteins were involved in actin cytoskeleton remodeling ( Colozza et al., 2020 ). To examine whether Wnt induced changes in the cytoskeleton, primary human corneal stromal (HCSF) fibroblasts ( Gallego-Muñoz et al., 2018 ) were treated with Wnt3a.…”
Section: Resultsmentioning
confidence: 99%
“…FlnA interacts with LRP6, and loss of FlnA impairs internalization of LRP6 and activation of Wnt/β-catenin signaling, resulting in decreased proliferation of neural progenitor cells ( Lian et al, 2016 ; Figure 3B ). Recently, LRP6 proximity proteins induced upon short-term Wnt3a treatment were identified using an LRP6-Apex2 fusion protein ( Colozza et al, 2020 ). Among them, Trk fused gene protein (TFG) appears to have an important role in Wnt3a-mediated LRP6 internalization and activation of Wnt/β-catenin signaling ( Colozza et al, 2020 ; Figure 3B ).…”
Section: Regulation Of Lrp6 Function and Downstream Signalingmentioning
confidence: 99%
“…Recently, LRP6 proximity proteins induced upon short-term Wnt3a treatment were identified using an LRP6-Apex2 fusion protein ( Colozza et al, 2020 ). Among them, Trk fused gene protein (TFG) appears to have an important role in Wnt3a-mediated LRP6 internalization and activation of Wnt/β-catenin signaling ( Colozza et al, 2020 ; Figure 3B ).…”
Section: Regulation Of Lrp6 Function and Downstream Signalingmentioning
confidence: 99%
“…Endocytosis is known to play a role in cancer by causing a loss of cell adhesion or morphological polarity, which can lead to the malignant transformation of cells [ 14 , 15 , 16 ]. For example, the small GTPases Rab proteins, which regulate vesicle transport, protein trafficking, membrane targeting and fusion, also mediate vesicle dynamics, which can work with oncogenic signaling pathways to increase tumor formation [ 17 , 18 , 19 , 20 ].…”
Section: Membrane Trafficking Lysosomes V-atpase and Macropinocytosis...mentioning
confidence: 99%